A new type of secondary hybrid battery showing excellent performances. (March 2015) - Yin, Yanli; Liu, Changhong; Fan, Shoushan
Abstract: The zinc-based primary batteries have various merits including the low cost, high-security and reasonable energy, but their one-time use and low power performance limit the wider applications. Compared with the primary batteries, the supercapacitor has an extra higher cycling performance and power capability, but its specific energy is lower. Here we originally achieve a novel hybrid battery combined of a zinc-based primary battery and a supercapacitor through a unique assembly method. In this new structure, two symmetrical carbon nanotube/polyaniline nanoporous composites as supercapacitor electrodes are inserted in a zinc–manganese dioxide primary battery system with a way in series. Meanwhile, a special technique is used to form excellent conductive connections between the supercapacitor electrodes and the primary battery cathode and anode, respectively. This hybrid battery shows both a high specific power similar to that of the supercapacitor and a high specific energy comparable to that of the primary battery. It is more striking that the rechargeable character of this hybrid battery is much more excellent. Its specific capacity retained 75% after 500 cycles of charge–discharge at the high current density of 2 A g −1 while the coulombic efficiency kept at 100%. These notable improvements are attributed to the special design on the structure and chemistry system of the hybrid battery combining the merits of both the primary battery and the supercapacitor. Graphical abstract: Highlights: We originally designed a hybrid battery combined of a zinc-based primary battery and a polymer supercapacitor through a quite simple assembly method. The polyaniline/carbon nanotube used as inserted supercapacitive layer has a unique nanoporous structure. A special technique is used to form excellent conductive connections between the electrodes of supercapacitor and primary battery. This hybrid battery shows excellent rechargeable character compared with the primary battery. A novel model is presented to explain the mechanism of the rechargeability of this hybrid battery.